Regional odontodysplasia - a rare developmental dental anomaly - Kacper Nijakowski; Anna Surdacka (Termedia Publishing House, 2021)
Regional odontodysplasia is a rare developmental dental anomaly affecting ectodermal and mesodermal tissues. Hypocalcification and hypoplasia are most often observed in one quadrant. The aetiology remains uncertain - the harmful local factor in the perinatal period is considered. It occurs more often in the maxilla, with a predisposition to females. The report presents a clinical case of a 5-year-old boy with regional odontodysplasia affecting deciduous and permanent dentition in the left quadrant of the mandible. The radiological image revealed characteristic "ghost teeth" in primary dentition and poorly developed buds of secondary teeth. Because of recurrent purulent inflammations, his milk teeth were surgically removed. In the literature, there is no consensus on the treatment of choice. However, it is suggested that affected teeth should not be extracted until inflammation occurs to allow the development of surrounding bone. Due to the age-related functional and aesthetic needs, the patients require long-term specialist care.